Dari Yogyakarta ke Pelosok Nagari: Aisyiyah dan Modernisasi Perempuan di Nagari Kubang (1930-1945) - Khairanis, Khairanis (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2024)
This article aims to provide an overview of the establishment of Aisyiyah in Yogyakarta and its development and role in Kenagarian Kubang, Minangkabau, during the period of 1930-1945. The women's movement in Indonesia has undergone a long historical evolution, and during the national movement era, women had established formal organizations dedicated to improving their conditions at that time. These formal organizations were not only city-based but also village-based, as exemplified by the Aisyiyah Organization in Kubang. As an autonomous organization under Muhammadiyah, Aisyiyah was granted the authority to manage charitable activities in the social, religious, educational, and vocational fields. This article analyzes how Aisyiyah contributed to enhancing the welfare and education of women in Kubang, as well as its role in the social and religious movements in the region.